Inequality and African-American health : how racial disparities create sickness - Hill, Shirley A. (Shirley Ann), 1947- (Policy Press, 2016)
"This book shows how living in a highly racialized society affects health through multiple social contexts, including neighborhoods, personal and family relationships, and the medical system. Black-white disparities in health, illness, and mortality have been widely documented, but most research has focused on single factors that produce and perpetuate those disparities, such as individual health behaviors and access to medical care. This is the first book to offer a comprehensive perspective on health and sickness among African Americans, starting with an examination of how race has been historically constructed in the US and in the medical system and the resilience of racial ideologies and practices. Racial disparities in health reflect racial inequalities in living conditions, incarceration rates, family systems, and opportunities. These racial disparities often cut across social class boundaries and have gender-specific consequences. Bringing together data from existing quantitative and qualitative research with new archival and interview data, this book advances research in the fields of families, race-ethnicity, and medical sociology"--Provided by publisher